Physical fitness attributes of team-handball players are related to Playing Position and Performance Level - Massuca, L.; Branco, B.; Miarka, B.; Fragoso, I. (Asian Journal of Sports Medicine, 2014)
Background: Investigations have reported differences amongst player position groups in elite team-Handball (HB) players. Nevertheless, studies with normative physical fitness data of the HB playing positions at more than two different levels of male HB players have not been reported yet.